Teacher Readiness Analysis for Implementing the Independent Learning Curriculum in Kindergarten - Aisyah, Aisyah; Puspa Juwita, Rani (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
The independent learning curriculum is a new curriculum designed to provide opportunities for children to learn in a calm, relaxed, fun, pressure-free manner and to show their natural talents. The purpose of this study is to find out how prepared teachers are in implementing the Independent Learning Curriculum in Dharma Wanita Kindergarten. The research method used is descriptive qualitative. The data collection techniques used in this research are observation, interviews and documentation. The data analysis technique used is in accordance with Miles and Huberman's opinion, consisting of data collection, data reduction, data presentation and conclusions. The research results showed that of the five indicators observed, Dharma Wanita Kindergarten teachers had good readiness in three indicators, namely learning plan indicators, learning processes and facilities and infrastructure. Meanwhile, for the other two indicators, namely the teaching module indicators and learning assessment, learning or training is still needed which can increase teachers' understanding of these two indicators